2016
DOI: 10.1039/c6cc02116f
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally water stable heterometallic gyroidal MOFs: tuning the porosity and hydrophobicity by doping metal ions

Abstract: A strategy to improve the framework porosity and hydrophobicity of the pore surface by doping metal ions (Cu(2+), Cd(2+), or Fe(2+)) into a gyroidal MOF STU-1 has been developed. It is found that the obtained heterometallic MOFs are exceptionally water stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 26 publications
(4 reference statements)
0
50
0
Order By: Relevance
“…Employing a similar strategy, a few metal ions, including Cu 2+ , Cd 2+ , and Fe 2+ , were separately doped into a gyroidal MOF, STU-1. 91 Unlike the poor hydrostability of pure STU-1, it was found that all metal doped STU-1s retained their morphology and crystallinity even aer soaking in boiling water for 7 days. Beyond that, aer doping with metal ions, the signicantly increased surface hydrophobicity of STU-1 was proved by water vapor adsorption isotherm curves.…”
Section: Chemical Stabilitymentioning
confidence: 83%
See 1 more Smart Citation
“…Employing a similar strategy, a few metal ions, including Cu 2+ , Cd 2+ , and Fe 2+ , were separately doped into a gyroidal MOF, STU-1. 91 Unlike the poor hydrostability of pure STU-1, it was found that all metal doped STU-1s retained their morphology and crystallinity even aer soaking in boiling water for 7 days. Beyond that, aer doping with metal ions, the signicantly increased surface hydrophobicity of STU-1 was proved by water vapor adsorption isotherm curves.…”
Section: Chemical Stabilitymentioning
confidence: 83%
“…There may be several reasons for this: (1) the formation of stronger coordination bonds compared with pristine bonds; (2) the enhancement of the inertness of metal clusters; (3) the improvement of surface hydrophobicity. 90,91 Hence, the design principle toward the fabrication of stable mixed-metal MOFs is the replacement of existing metal ions with more inert species.…”
Section: Chemical Stabilitymentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) or porous coordination polymers are crystalline porous materials composed of metal ions or clusters connected three-dimensionally by multi-topic organic ligands. [13][14][15][16][17][18][19][20] This hybrid architecture opens the possibility to design and synthesize a great variety of new porous materials. 21,22 As a result, MOFs are highly attractive components for advanced structures and functionalized materials for applications including catalysis, 23,24 drug delivery, 25,26 sensing, 27 and gas separation.…”
Section: Introductionmentioning
confidence: 99%
“…No loss of crystallinity in STU‐5 was observed by PXRD measurements after the sample was treated at 550 °C, boiling water or methanol for 24 h. The authors believed that the introduction of hydrophobic methyl groups on the pore surface resulted in the enhanced water stability of STU‐5 compared to that of STU‐1. Recently, the group reported that the hydrophobicity and water stability of STU‐1 could be improved by doping metal ions (Cu 2+ , Cd 2+ , or Fe 2+ ) into its framework . The metal ions were doped by their introduction to the synthetic reaction mixture of STU‐1, unlike some published works reporting the postsynthetic exchange of metal ions in the frameworks of MOFs .…”
Section: Preparation Of Hydrophobic Mofsmentioning
confidence: 99%
“…Recently, the group reported that the hydrophobicity and water stability of STU-1 could be improved by doping metal ions (Cu 2+ , Cd 2+ , or Fe 2+ ) into its framework. [218] The metal ions were doped by their introduction to the synthetic reaction mixture of STU-1, unlike some published works reporting the postsynthetic exchange of metal ions in the frameworks of MOFs. [219,220] However, doping STU-1 with Mn 2+ , Co 2+ , and Ni 2+ by the one-pot synthesis method was found to be unsuccessful.…”
Section: In Situ Synthetic Hydrophobizationmentioning
confidence: 99%